Der italienische Staat und die Freikirchen - Long, Gianni (Kirchliche Zeitgeschichte, 2000)
An overview of the history of the legal relationships between the Italian State and the Free Churches shows a considerable variety of arrangements before 1848, but, after that date, there followed the emancipation of the Jews and the Waldensians, and the placing of the religious minorities under the scope of the liberal "common law". In 1929 the fascist government signed a Concordat with the Vatican and thereby solved the "Roman question". This also enabled those religious communities which had previously been only "tolerated" to now become "accepted corporations", even though their freedoms were still restricted. The republican constitution of 1948 sought to extend the rights of non-Catholics. But only in 1976, when the Concordat was revised, could a new legal relationship for the Waldensians and the Methodists be worked out. This proved to open the way for other religious minorities, both Jewish and Christian. Later on the same pattern was applied to the Buddhists and the Jehovah's Witnesses. In summary, on the one hand, there is no conflictual situation in Italy between Volkskirche and Free Churches. Instead there is a series of four stages of legal safeguards, from the privileged Catholic Church down to those communities without any legal recognition. On the other hand, this inequality means a considerable freedom over all.